Towards greener telecommunication towers: A framework for "LEED for telecom towers". Issue 1 (31st December 2023) - Elhakim, Yasmin; Hazem, Nahla; Ismail, Tawfik; Mahmoud, Mohamed; Fahim, Irene
Abstract: As climate change becomes an urgent issue that must be tackled immediately, several disciplines are making efforts to mitigate its effects. One of the disciplines that must be addressed to mitigate the negative impacts it has on the environment is the installation of telecommunication towers. An ever-increasing number of telecommunication towers may have negative impacts on the environment because of the use of diesel, not environmentally friendly materials or the waves emitted to the surrounding environment. Literature review showed different sustainable approaches that were proposed for use in telecommunication towers. However, there is a gap in having a comprehensive approach for making the overall factors of the telecommunication towers more sustainable. Green rating systems are used as guidelines for making buildings more sustainable. Leadership in Energy and Environmental Design (LEED) rating system is the most widely used green rating system in the world; however, it doesn't have any guidelines for applying sustainable measures in telecommunication towers. Therefore, this paper proposes a green rating system that is based on LEED's main categories, to limit the negative impacts telecommunication towers have on the environment. Then, 21 questionnaires were distributed among engineers from various backgrounds in Egypt as a case study to come up with proposed weights for categories and subcategories. The questionnaire analysis is based on Analytical Hierarchy Process. It is concluded that the sustainable site category has the highest weight, as the optimum selection of site would help in improving the overall factors that affect the environmental behavior of the tower.